Analysis of Biogas Assistance Program in Dairy Farm Development - Dila Ananda Syabillah; Mochamad Ali Mauldin; Marina Sulistyati (Journal La Sociale, 2024)
Corporate Social Responsibility (CSR) is a form of corporate social responsibility towards the community and environment around the company. The biogas assistance program is one of PJT II's CSR programs in order to accelerate the handling of damage to the Citarum river watershed (DAS) and for the purpose of empowering the community, especially dairy farmers who come from members of the KPBS Pangalengan dairy farmer group. The aim of this research is to determine the mechanism for implementing the biogas assistance program as part of CSR activities and to analyze the benefits of implementing the biogas assistance program in developing the sustainability of dairy farming businesses. This research was conducted in November – December 2023. This research was conducted using a qualitative approach using the case study method. Primary data was obtained through in-depth interviews with informants selected purposively from twenty-one people consisting of the company, participants receiving assistance and implementing parties. The results of the research show that the implementation of the biogas assistance program has been implemented through a process planning, organizing, actuating, controlling (POAC) in the program mechanism, apart from that, the analysis of the program's objectives is to reduce pollution and damage to the Citarum watershed as a result of breeder activities and provide opportunities to increase income independently and sustainably and is an effort to increase breeder awareness to better protect the surrounding environment so that it can speed up the handling of damage to river watersheds that is currently occurring.